Relationship Between Plasma Vitamin C and COVID-19 Susceptibility and Severity: A Two-Sample Mendelian Randomization Study - Chen, Song; Zheng, Changhua; Chen, Tianlai; Huang, Dianhua; Pan, Yuancheng; Chen, Shunyou (Frontiers in Medicine, 2022)
Background: Vitamin C, also called ascorbic acid, due to its antioxidant function is widely used in viral infections like Coronavirus disease (COVID-19) based on in vitro, observational, and ecological studies. There are many confounding factors that can affect Vitamin C levels, and thus the association described to date may not be causal. To determine the causal relationship between genetically predicted plasma Vitamin C and COVID-19 susceptibility and severity, we performed the two-sample Mendelian randomization (MR) based on large samples. Methods: The summary-levels data for Vitamin C was obtained from a GWAS meta-analysis, which included 52,018 individuals from 4 studies of European ancestry. Data for COVID-19 HGI results was obtained from the Meta-analysis of 35 GWASs with more than 1,000,000 subjects of European ancestry, including 32,494 cases with COVID-19 susceptibility and 1,316,207 controls, 9,986 cases with COVID-19 hospitalization and 1,877,672 controls, and 5,101 cases with COVID-19 severe disease and 1,383,241 controls. A Mendelian randomization (MR) analysis was conducted to examine the effect of selected single nucleotide polymorphisms (SNPs) and COVID-19 susceptibility; hospitalization; severe disease. Several sensitivity analyses were performed with inverse-variance weighted (random-effect model); Inverse variance weighted (fixed-effect model), weighted median and Maximum likelihood methods for estimating the causal effects. Results: In this MR study, genetic predisposition to the levels of plasma Vitamin C was not associated with COVID-19 susceptibility (OR: 0.99, 95% CI: 0.84-1.17, P value=0.91), hospitalization (OR: 1.10, 95% CI: 0.71-1.71, P value= 0.67) and severity (OR: 0.83, 95% CI: 0.43-1.59, P value=0.58). The association was consistent in complementary analyses. There were no potential heterogeneities and no directional pleiotropies for the analysis results. Conclusion: According to our study, no correlation was observed between plasma Vitamin C levels and COVID-19 susceptibility and severity. Further studies in different ethnics are necessary to explore the potential role and mechanisms of circulating serum Vitamin C levels on COVID-19.